Surveillance of Bacillus cereus Isolates in Korea from 2012 to 2014 - Jung, Su-Mi; Kim, Nan-Ok; Cha, Injun; Chung, Gyung Tae; Kawk, Hyo Sun; Hong, Sahyun (Osong public health and research perspectives, 2017)
To investigate the prevalence and toxin production characteristics of non-emetic and emetic strains isolated via the laboratory surveillance system in Korea. A total of 667 strains were collected by the Korea National Research Institute of Health laboratory surveillance system from 2012 to 2014. The collected strains were analyzed by geographical region, season, patient age, and patient sex. Additionally, the prevalence rates of enterotoxin and emetic toxin genes were evaluated. The isolation rate of strains increased during the summer, but the isolation rate was evenly distributed among patient age groups. Emetic toxin was produced by 20.2% of the isolated strains. The prevalence rates of five enterotoxin genes ( , , , , and ) were 85.0, 78.6, 44.5, 36.6, and 29.7%, respectively, among non-emetic strains and 77.8, 59.3, 17.8, 11.9 and 12.6%, respectively, among emetic strains. Thus, the prevalence rates of all five enterotoxin genes were lower in emetic . The prevalence of enterotoxin genes differed between non-emetic and emetic strains. Among emetic strains, the prevalence rates of two enterotoxin genes ( and ) were lower than those among the non-emetic strains. In both the emetic and non-emetic strains isolated in Korea, and were the most prevalent enterotoxin genes.